Targeting Future Pandemics, a Case for De Novo Purine Synthesis and Basic Research - Mazzarino, Randall C. (Frontiers in Immunology, 2021)
We are currently experiencing a deadly novel viral pandemic with no efficacious, readily available anti-viral therapies to SARS-CoV-2. Viruses will hijack host cellular machinery, including metabolic processes. Here, I provide theory and evidence for targeting the host de novo purine synthetic pathway for broad spectrum anti-viral drug development as well as the pursuit of basic science to mitigate the risks of future novel viral outbreaks.